The Three Paths of Justice Court Proceedings, Arbitration, and Mediation in England - Andrews, Neil (Ius Gentium: Comparative Perspectives on Law and Justice,, 2018)
This revised second edition takes account of developments in the field of dispute resolution, including mediation and arbitration. The book presents a concise account of the English system of civil litigation, covering court proceedings in England and Wales. It is an original and important study of a system which is the historical root of the US litigation system. The volume offers a comprehensive and properly balanced account of the entire range of dispute resolution techniques. As the first (revised) book on this subject to be published in the USA, it enables American lawyers to gain an overview of the main institutions of English Civil Procedure, including mediation and arbitration. It will render the English system of civil justice accessible to law students in the US, practitioners of law, professors, judges, and policy-makers.